Economic valuation of a dehydrated fruit marketing plan - Bravo, Maria Belen (mktDESCUBRE, 2020)
This research aims to develop a marketing plan for dehydrated fruits, specifically strawberry and apple applied in Riobamba, descriptive methodology was used using the technique of direct observation and application of surveys validated by crownbach alpha coefficient; directed to potential clients, distributed in sectors north, south and center of the city, where the factors that affect the commercialization of dehydrated fruits were known. A current analysis of dehydrated fruit commercialization, market study, strategic plan, marketing plan, operational plan was carried out, where the unmet demand was determined to be 60.00%. With the financial study it was determined the income for the year 2019 will be 179 810.04 dollars, the Net Present Value obtained is 158 200.19 dollars, an Internal Rate of Return of 34.14%; the benefit-cost ratio of $ 1.25; It was concluded that the marketing and commercialization plan for dehydrated fruits in the city of Riobamba is feasible.